Transcranial alternating current stimulation to the inferior parietal lobe decreases mu suppression to egocentric, but not allocentric hand movements. (6th March 2017) - Berntsen, Monica B.; Cooper, Nicholas R.; Romei, Vincenzo
Highlights: Neurophysiological responses to observation of movement depend on perspective. Egocentric is considered self-related while allocentric relates to others. IPL has been related to self-other differentiation. tACS to IPL reduces mu-suppression to egocentric but not allocentric movements. Abstract: Egocentric vs. allocentric perspective during observation of hand movements has been related to self-other differentiation such that movements observed from an egocentric viewpoint have been considered as self-related while movements observed from an allocentric viewpoint have been considered as belonging to someone else. Correlational studies have generally found that egocentric perspective induces greater neurophysiological responses and larger behavioral effects compared to an allocentric perspective. However, recent studies question previous findings by reporting greater (μ) suppression and greater transcranial magnetic stimulation (TMS)-induced motor-evoked potentials (MEPs) during observation of allocentric compared to egocentric movements. Furthermore, self-other differentiation has been generally related to activity within the inferior parietal lobe (IPL), but direct evidence for a causal and functional role of IPL in self-other differentiation is lacking. The current study was therefore designed to investigate the influence that IPL exerts on self-other differentiation. To this aim, we measured the impact of individually adjusted alpha-tuned transcranial alternating current stimulation (tACS) applied over IPL on μ-suppression during hands movement observation from an egocentric and allocentric perspective. Electroencephalography (EEG) was recorded during movement observation before and immediately after tACS. Results demonstrated that tACS decreased μ-reactivity over sensorimotor (but not visual) regions for egocentric (but not allocentric) movement observation providing direct evidence for a causal involvement of IPL in the observation of self- but not other-related hand movement.